2006
DOI: 10.3748/wjg.v12.i21.3416
|View full text |Cite
|
Sign up to set email alerts
|

Role of soluble triggering receptor expressed on myeloid cells in inflammatory bowel disease

Abstract: sTREM-1 seems to behave as a novel mediator in IBD in correlation with the degree of the inflammatory reaction of the intestinal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 16 publications
4
46
0
1
Order By: Relevance
“…Increased levels of soluble TREM-1 (sTREM-1) were found in patients or animals with infectious and non-infectious diseases, and were correlated with disease severity. [10][11][12] Serum sTREM-1 was found to be higher in patients with AP than in healthy volunteers. [13] Thus, it is important to investigate the role of TREM-1 in the development of SAP associated with IBD.…”
Section: Discussionmentioning
confidence: 91%
“…Increased levels of soluble TREM-1 (sTREM-1) were found in patients or animals with infectious and non-infectious diseases, and were correlated with disease severity. [10][11][12] Serum sTREM-1 was found to be higher in patients with AP than in healthy volunteers. [13] Thus, it is important to investigate the role of TREM-1 in the development of SAP associated with IBD.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, two other studies revealed a correlation between sTREM-1 level and clinical disease activity in IBD. 17,18 Numerous studies have shown that TNF-a plays a central immunopathogenetic role in systemic BD, and anti TNF-a agents have been shown to be effective in the treatment of systemic BD patients. [19][20][21][22][23]34 Elevated serum levels of TNF-a have been reported by several groups in patients with active BD; these studies indirectly suggested that the TNF-a level might correlate closely with clinical disease activity in systemic BD.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, two other studies have described a correlation between sTREM-1 and clinical disease activity in IBD. 17,18 These studies suggest that sTREM-1 may play a role in the disease pathogenesis and progression of IBD. Based on the above evidence, we hypothesized that sTREM-1 could be a potential biological marker for the assessment of disease activity in intestinal BD.…”
mentioning
confidence: 94%
“…Recently, increased serum levels of sTREM-1 were reported in patients with moderate or severe UC and CD (26). This further indicates that increased TREM-1 expression may closely reflect the extent of intestinal inflammation and may thus represent an elegant tool to monitor disease activity.…”
Section: Figurementioning
confidence: 92%